Unraveling geographical heterogeneity and spatial distribution of Long pepper fruits: An integrative analytical perspective - Shuwen Geng; Conghui Duan; Ying Ye; Yuye Gao; Yujia Zhai; Fangyuan Gao; Yuewei Ge; Yang Chen; Yunxia Li; Rongping Zhang; Xinglong Chen; Jian-lin Wu; et al. (Food Chemistry, 2026)

Response characteristics of antibiotic resistance genes and bacterial communities during agricultural waste composting: Focusing on biogas residue combined with biochar amendments - Yuewei He; Xiaowei Yin; Fanghong Li; Bo Wu; Ling Zhu; Dabing Ge; Nanyi Wang; Anwei Chen; Lihua Zhang; Binghua Yan; Hongli Huang; Lin Luo; et al. (Bioresource Technology, 2023)

Correction to: Search of anti-allodynic compounds from Plantaginis Semen, a crude drug ingredient of Kampo formula “Goshajinkigan” - Kazufumi Toume; Zhiyan Hou; Huanhuan Yu; Mitsuru Kato; Miki Maesaka; Yanjing Bai; Shiho Hanazawa; Yuewei Ge; Tsugunobu Andoh; Katsuko Komatsu (Journal of Natural Medicines, 2020)
The article Search of anti-allodynic compounds from Plantaginis Semen, a crude drug ingredient of Kampo formula “Goshajinkigan”.

Lysine acetylation contributes to development, aflatoxin biosynthesis and pathogenicity in Aspergillus flavus - Guang Yang; Yuewei Yue; Silin Ren; Mingkun Yang; Yi Zhang; Xiaohong Cao; Yinchun Wang; Jia Zhang; Feng Ge; Shihua Wang (Environmental Microbiology, 2019)
Summary Aspergillus flavus is a pathogenic fungus that produces carcinogenic aflatoxins, posing a great threat to crops, animals and humans. Lysine acetylation is one of the most important reversible post‐translational modifications and plays a vital regulatory role in various cellular processes. However, current information on the extent and function of lysine acetylation and aflatoxin biosynthesis in A. flavus is limited. Here, a global acetylome analysis of A. flavus was performed by peptide pre‐fractionation, pan‐acetylation antibody enrichment and liquid chromatography–mass spectrometry. A total of 1313 high‐confidence acetylation sites in 727 acetylated proteins were identified in A. flavus . These acetylation proteins are widely involved in glycolysis/gluconeogenesis, pentose phosphate pathway, citric acid cycle and aflatoxin biosynthesis. AflO ( O ‐methyltransferase), a key enzyme in aflatoxin biosynthesis, was found to be acetylated at K241 and K384. Deletion of aflO not only impaired conidial and sclerotial developments, but also dramatically suppressed aflatoxin production and pathogenicity of A. flavus . Further site‐specific mutations showed that lysine acetylation of AflO could also result in defects in development, aflatoxin production and pathogenicity, suggesting that acetylation plays a vital role in the regulation of the enzymatic activity of AflO in A. flavus . Our findings provide evidence for the involvement of lysine acetylation in various biological processes in A. flavus and facilitating in the elucidation of metabolic networks.

Search of anti-allodynic compounds from Plantaginis Semen, a crude drug ingredient of Kampo formula “Goshajinkigan” - Kazufumi Toume; Zhiyan Hou; Huanhuan Yu; Mitsuru Kato; Miki Maesaka; Yanjing Bai; Shiho Hanazawa; Yuewei Ge; Tsugunobu Andoh; Katsuko Komatsu (Journal of Natural Medicines, 2019)